Atopy as an independent predictor for long-term patient and graft survival after kidney transplantation - Porret, Raphaël; Meier, Raphaël P. H.; Mikulic, Josip; Pascual, Manuel; Aubert, Vincent; Harr, Thomas; Golshayan, Déla; Muller, Yannick D. (Frontiers in Immunology, 2022)
Background. Atopy is a genetic condition predisposing individuals to develop immunoglobulin E (IgE) against common allergens through T-helper 2 (Th2) polarization mechanisms. The impact of atopy on graft survival in solid organ transplantation is unknown. Methodology. We analyzed 268 renal allograft recipients from the Swiss Transplant Cohort Study, a prospective multicenter cohort studying patients after solid organ transplantation, with a 9-year median follow-up (IQR 3.0). We used the Phadiatop assay to measure IgE antibodies against a mixture of common inhaled allergens (grass, tree, herbs, spores, animals, and mites) to identify pre-transplantation atopic patients (>0.35 KU/L). Results. Of 268 kidney transplant recipients, 66 individuals were atopic (24.6%). Atopic patients were significantly younger than non-atopic patients (49.6 vs 58.0 years old, P = 0.002). No significant difference was found for gender, cold/warm ischemia time, preformed donor-specific antibodies (DSA), HLA mismatches, induction and maintenance immunosuppressive therapy, CMV serostatus, or cause of kidney failure. Patient and graft survival at ten years of follow-up were significantly better in the atopic group, 95.2% versus 69.2% patient survival (P < 0.001), and 87.9% versus 60.8% graft survival (P < 0.001), respectively. A multivariate Cox analysis revealed that atopy predicted recipient and graft survival independently of age and living donor donation. Finally, we found similar rates of biopsy-proven acute cellular and antibody-mediated rejections between atopic and non-atopic recipients. Conclusion. Atopy was associated with better long-term patient and graft survival, independently of age and living donor donation after kidney transplantation. Yet, atopy should not be used as a predictor for acute rejection.